The benefits of intergenerational Programmes from the perspective of the professionals - Marta Gutiérrez Sánchez; Daniel Hernández Torrano (Sociedad Iberoamericana de Pedagogía Social, 2013)
Research in the field of intergenerational programmes has shown that the relationship between individuals of different generation has a very positive impact on those directly involved in it. Intergenerational programmes have shown to be effective, for example, increasing the elderly's psychological, physical, and social wellbeing, and changing young people's perceptions about the elderly. The present study examines the impact of intergenerational programmes on those directly involved in them- children, adolescents, and elderly - as well as those that participate in the intergenerational relationship indirectly - family, professionals, and society - from the perspective of the professionals who work on the programmes. A qualitative design based on data collected through semi-structured interviews to 25 professionals who coordinated intergenerational programmes in Spain was used. The content analysis of the information provided by the professionals evidenced four dialectical dimensions on this study: impact on participants, impact on families, impact on professionals, and intergenerational connection. Finally, some conclusions on the importance of inquiring about the impact of these programmes on all those involved in intergenerational relationships are provided.